A novel P-norm correction method for lightweight topology optimization under maximum stress constraints. (15th July 2016) - Lee, Kangwon; Ahn, Kisoo; Yoo, Jeonghoon
Highlights: We present maximum stress constrained topology optimization using a novel P-norm correction method for lightweight design. A modified P-norm correction method is proposed to overcome the limitation of conventional P-norm methods by using the lower and the upper bound P-norm stress curve. Lightweight designs are presented for the L-shaped and the cantilever beam subject to yield strength constraint for the verification of the proposed method. Abstract: This study presents maximum stress constrained topology optimization using a novel P-norm correction method for lightweight design. The phase field design method with double well potential functions is used to implement structural optimization. We propose a modified P-norm correction method to overcome the limitation of conventional P-norm methods by employing the lower bound P-norm stress curve. As a result, maximum stress value can be considered as a design constraint effectively. For the verification of the proposed method, lightweight designs are presented for the L-shaped and the cantilever beam with the yield strength constraint.